Coconut Fiber Cement Panels as Wall Insulation and Structural Diaphragm - Brose, Andrew; Kongoletos, Johnathan; Glicksman, Leon (Frontiers in Energy Research, 2019)
This study considers the applications of natural fiber composites in affordable housing projects located in the two districts of Gujarat, India, and Gorkha, Nepal, with the goal of addressing issues of thermal comfort and lateral loading from seismic activity. To help alleviate some of these issues, the team worked with the Hunnarshala Foundation, in Bhuj, India, to develop a fiber cement composite that could be applied to the interior or exterior of a home and provide both insulative and structural improvements. Thermal conductivity of the composites comprised of various mixes were measured using a heat flux machine. Experimental results of 0.16–0.19 W/m·K showed an improvement in thermal conductivity compared to current wall cladding materials ranging from 1.60 to 1.88 W/m·K. Modeling of the building envelope was completed using the EnergyPlus™ tool and showed that homes using the fiber cement composites would have an overall reduction in heating and cooling requirements. The study used coconut husk fibers (referred to as coconut coir), rattan, and pine wood fibers in addition to Portland cement, fly ash, and hydrated lime in the fabrication of fiber cement composite samples. Flexural strength of natural fiber samples was 70% stronger than comparison specimens, suggesting possible application for wall cladding to reduce out-of-plane failure during seismic events. Field tests conducted in Gujarat validated lab results as well as qualitative perceptions of the material. Continued work with local partners presents several possible applications of coconut coir fiber cement composites for retrofit and new construction housing.